Psoriatic arthritis and COVID-19: a new challenge for rheumatologists and dermatologists - Zohreh Jadali (BMC, 2024)
Abstract COVID-19 has changed the global health system and has great impact on different types of medical specialties including, dermatology and rheumatology. This point is important because although these two specialties are distinct subfields of medicine, there is some overlap between them. The overlap can be described by a number of rheumatic diseases that have cutaneous manifestations and vice versa. A good example of this is psoriatic arthritis because, in up to 42% of people, cutaneous lesions and arthritis coexist. Interestingly, emerging reports have described the possible occurrence of psoriasis and psoriatic arthritis in COVID-19 patients. Although the exact mechanism is unclear, some common pathophysiological mechanisms may contribute to disease pathogenesis. Therefore, elucidation of shared pathological pathways that connect these diseases will be valuable for better diagnosis and the complete treatment of COVID-19 patients with cutaneous and rheumatologic diseases.